Legal Review of the Four Orderly Land Procedures in the Field of Absentee Land Ownership - Setyawan, Joseph Ryan; Hasana, Dahniarti (Jurnal Konstatering, 2025)
Abstract.This study aims to analyze: 1) Implementation of the Catur Tertib Pertanahan policy on absentee land ownership in Demak Regency. 2) Obstacles and solutions in the implementation of the Catur Tertib Pertanahan program in overcoming absentee land ownership in Demak Regency. This type of research is included in the scope of empirical legal researcp. The approach method in this study is a sociological legal approacp. The types of data in this study are primary and secondary data sourced from primary, secondary and tertiary legal materials. The data collection method uses interview and literature techniques (study documents). The analysis in this study is prescriptive. The results of the study concluded: 1) The implementation of the Catur Tertib Pertanahan policy on absentee land ownership in Demak Regency aims to create legal certainty, equal distribution of land control, and optimal land use in accordance with the principles of social justice. Various regulations have regulated the prohibition of absentee land ownership, including Law Number 5 of 1960 concerning Basic Agrarian Regulations and Government Regulation Number 224 of 1961. Local governments, through the National Land Agency (BPN) and related agencies, conduct data collection, supervision, and land redistribution to ensure that land owned absentee can be allocated to farmers who need it more. However, the implementation of this policy still faces various challenges, especially in terms of law enforcement, land administration, and social and cultural factors in the community. 2) The implementation of this program faces several obstacles, including legal loopholes that allow landowners to avoid regulations, weak law enforcement, and lack of validity of land ownership data. In addition, limited coordination between institutions and low legal awareness in the community also hamper the effectiveness of this policy. To overcome these problems, solutions that can be applied include revising regulations to strengthen rules and sanctions, increasing supervision through digital systems, and optimizing coordination between local governments, BPN, and law enforcement. Education and outreach to the community also need to be improved so that understanding of this policy is broader. With these various strategic steps, the implementation of the Catur Tertib Pertanahan in Demak Regency can run more effectively in overcoming absentee land ownership, so that land distribution becomes fairer and its utilization is more optimal.Keywords: Absentee Land; Election; Land; Rights; Orderly Chess.